Social conditions in Iraq In the years of the Second World War 1939-45 (Journal of the College of Basic Education, 2023)
Most of the historical studies in our academic institutions focused on the study of aspectsPolitics and economics, while the social aspects did not receive a significant share of attention.Undoubtedly, getting to know the social conditions will provide us with a measure of the possibility of getting to know each other.The extent of the impact of the political and economic conditions on society and its movement, and the attitude of individuals towardsthe overall political and economic developments, given that social conditions are nothing butA reflection of the political and economic events in people's lives.The importance of this research comes in that it tries to present a closer picture of the effect ofThe Second World War and the political and economic developments that attached it to lifesociety in Iraq. Taking into account that Iraq was not a direct party orEssentially in that war, although its impact affected, in one way or another, the facilities of life in the country.then.